Luteal Phase Support Using Subcutaneous Progesterone: A Systematic Review - Conforti, Alessandro; Carbone, Luigi; Iorio, Giuseppe Gabriele; Cariati, Federica; Bagnulo, Francesca; Marrone, Vincenzo; Strina, Ida; Alviggi, Carlo (Frontiers in Reproductive Health, 2021)
Luteal phase support is crucial in ART cycles where luteal phase has been found to be defective. This deficiency is probably related to the supraphysiological steroid levels that usually occurred in stimulated cycles that in turn could severely affect luteinizing hormone secretion and function thereby negatively influencing luteal phase. Several randomized controlled trials and meta-analysis clearly demonstrated that luteal phase support is associated with significantly higher live births comparing with placed or no treatment. Different medications and routes have been successfully used for luteal phase support in ART. Although the optimal protocol has not yet been identified, such plethora of medications offers the opportunity to personalize luteal phase support according to the individual needs. Subcutaneous administration progesterone was proposed for luteal phase support and could represent an alternative to vaginal and intramuscular route. The aim of the present systematic review is to summarize the literature evidence concerning the application of subcutaneous progesterone in ARTs pointing out the benefits and the limits of this novel strategy.